The Effects of GRDP, Wages, Human Resource Quality and Population on Labor Absorption - Elansa, Marlia Oktafia; Fitanto, Bahtiar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
An increase in unemployment characterizes a suboptimal level of labor absorption in an economy. This situation will bring serious problems to the economy and cause other problems. This study aims to determine the effect of GRDP, wages, human resource quality, and population on labor absorption in regencies/cities in East Java. This study uses descriptive quantitative analysis with panel data regression analysis tools. Data sourced from the BPS for the period 2017-2023 and consisting of 38 regencies/cities in East Java. The results of the study indicate that GRDP has a significant and positive effect on labor absorption, human resource quality has a significant and positive effect on labor absorption, and population has a significant and positive effect on labor absorption. Meanwhile, wages have a negative and insignificant effect on labor absorption, so wages will not influence labor absorption. Then, GRDP, wages, human resource quality, and population simultaneously have an impact on labor absorption in regencies/cities in East Java province.